Attenuation of N-nitrosodiethylamine-induced liver carcinogenesis in rats by naturally occurring diallyl sulfide (International Journal of Medicine and Medical Sciences, 2020)
The present study was aimed to investigate the chemopreventive effects of diallyl sulfide (DAS), organosulfur compounds present in high amounts in garlic, against N-nitrosodiethylamine (NDEA) induced hepatocarcinogenesis in rats. NDEA treatment to rats resulted in significantly elevated levels of serum aspartate transaminase, alkaline phosphatase, lactate dehydrogenase and sorbitol dehydrogenase along with significant decrease in serum total protein and albumin/globulin ratio, which are indicative of hepatocellular damage. Hepatic malondialdehyde and nitric oxide levels were also elevated. Hepatic glutathione, protein thiol, glutathione reductase, glutathione peroxidase, glutathione-S-transferase, gammaglutamyl cysteine synthetase and gammaglutamyl transferase were significantly increased in NDEA-treated group as compared to the control rats indicating disturbances in oxidant/antioxidant status. A significant decrease in hepatic ATP level was recorded indicating failure of energy metabolism. Administration of DAS to the NDEA- treated rats resulted in restoration of most of enzymatic and non enzymatic liver function tests. Also, liver content of most of the measured oxidants and antioxidant systems, enzymatic as well as non enzymatic, were normalized. Moreover, administration of DAS to NDEA-treated rats showed significant increase in pyruvate, ATP contents and lactate dehydrogenase activity, along with decrease in lactate and lactate/pyruvate ratio as compared to NDEA-treated rats. The histopathological examination of the liver sections confirmed these results. In conclusion, DAS could attenuate NDEA- induced hepatocarcinogenesis by improving the oxidant/antioxidant balance as well as the energy status of the hepatic tissue.